A realistic interpretation of magnetic and paleomagnetic data: A study of basalts from Southern Slovakia - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2021)
Basaltic rocks of the Pleistocene to Quaternary age from 38 localities from volcanic fields of southern Slovakia were studied. Except of the Curie temperature measurements of Fe-Ti oxides and the thermal demagnetization tests, also the hysteresis properties of selected samples of basalts were investigated. The basalts from 33 localities (87%) were reversely magnetized, basalts from only 5 localities acquired originally normal remanent magnetic polarization (RMP). A very soft selection of magnetic phases has allowed to categorize the basalts into 6 groups with different magnetic properties and direction of RMP. The results have lead to the suggestion that the reversed RMP of basalts is a consequence of the self-reversal process acting during the magnetization of cooling rocks in the normal polarity geomagnetic field. Some basalts of originally reversed RM were re-heated during repeated volcanic activity, and they were remagnetized. They acquired either normal polarity of the RMP, or they attained extremely anomalous directions of the RMP.